The Influence of Return on Asset, Debt to Equity Ratio, Earnings per Share, and Company Size on Share Return in Property and Real Estate Companies - Agung Tri Atidhira; Andi Ina Yustina (JAAF (Journal of Applied Accounting and Finance), 2017)
Capital market existence in Indonesia is marked with to the number of investor that start inculcates its share in industry real estate and property. Growing fast its sector growth this property is followed with growing request height of board need, until make investors property requires fund from external source. Fund was from external source can be obtained pass by capital market. The objectives of this research to analyze the influence of Return on Asset (ROA), Debt to Equity Ratio (DER) Earnings per Share and Company size on share return of real estate and property industry in Indonesia. The number of population for this research is 50 companies and the number of sample that examined after passed the purposive sampling phase is 35 companies. Analyze technique to use in this research is multiple linier regression to obtain picture which totally regarding relationship between one variable with other variable. The result of this research shows Debt to Equity Ratio (DER) and Earnings per Share (EPS) variables has a positive and significant influence to share return. On other hand, Return On Asset (ROA) and Company size has a negative and insignificant influence on share return on property and real estate industry. This result is expected that Return on Asset (ROA), Debt to Equity Ratio (DER) Earnings per Share (EPS) and Company size variable can be made reference, both by company management and also by investors in determining investment strategy.